TGF‐β1 downregulation in the hypothalamus of obese mice through acute exercise. Issue 10 (29th May 2019) - Silva, Vagner R. R.; Lenhare, Luciene; Katashima, Carlos K.; Morari, Joseane; M‐Assis, Alexandre; Gaspar, Rodrigo S.; da Silva, Adelino S. R.; Moura, Leandro P.; Pauli, José R.; Cintra, Dennys E.; Velloso, Licio A.; Ropelle, Eduardo R.
Abstract: Obesity and aging lead to abnormal transforming growth factor‐β1 (TGF‐β1) signaling in the hypothalamus, triggering the imbalance on glucose metabolism and energy homeostasis. Here, we determine the effect of acute exercise on TGF‐β1 expression in the hypothalamus of two models of obesity in mice. The bioinformatics analysis was performed to evaluate the correlation between hypothalamic Tgf‐β1 messenger RNA (mRNA) and genes related to thermogenesis in the brown adipose tissue (BAT) by using a large panel of isogenic BXD mice. Thereafter, leptin‐deficient ( ob/ob ) mice and obese C57BL/6 mice fed on a high‐fat diet (HFD) were submitted to the acute exercise protocol. Transcriptomic analysis by using BXD mouse reference population database revealed that hypothalamic Tgf‐β1 mRNA is negatively correlated with genes related to thermogenesis in brown adipose tissue of BXD mice, such as peroxisome proliferator‐activated receptor gamma coactivator and is positively correlated with respiratory exchange ratio. In agreement with these results, leptin‐deficient ( ob/ob ) and HFD‐fed mice displayed high levels of Tgf‐β1 mRNA in the hypothalamus and reduction of Pgc1α mRNA in BAT. Interestingly, an acute exercise session reduced TGF‐β1 expression in the hypothalamus, increased Pgc1α mRNA in the BAT and reduced food consumption in obese mice. Our results demonstrated that acute physical exercise suppressed hypothalamic TGF‐β1 expression, increasing Pgc1α mRNA in BAT in obese mice. Abstract : Obesity conditions increased transforming growth factor‐β1 (TGF‐β1) messenger RNA in the hypothalamus of obese mice; acute exercise reduces TGF‐β1 protein content and decreased food consumption in obese mice.